2021
DOI: 10.3390/ijerph18126355
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rotating Night Shift Work with Body Fat Percentage and Fat Mass Index among Female Steelworkers in North China

Abstract: The aim of this study was to evaluate the associations of rotating night shift work with body fat percentage (BF%) and fat mass index (FMI). A cross-sectional study was conducted among 435 female steelworkers, aged 26–57 years in Tangshan, China. BF% was assessed via bioelectrical impedance analysis and FMI was calculated. Different exposure metrics of night shift work were used to examine the effects of night shift work on BF% and FMI. The duration (years), cumulative number (nights), and cumulative length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The measurement criteria of height, weight, waist circumference and hip circumference (HC) in this study were shown in our previous study 20 . The detailed definitions of BF%, FMI, BMI, waist-to-hip ratio (WHR) and waist-to-height ratio (WHtR) have been elaborated in our previous study 20 . Blood pressure measurements were performed three times five-minute intervals using an electronic sphygmomanometer (OMRON, HBP-1100, China), and the participants were required to rest for more than ten minutes.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations
“…The measurement criteria of height, weight, waist circumference and hip circumference (HC) in this study were shown in our previous study 20 . The detailed definitions of BF%, FMI, BMI, waist-to-hip ratio (WHR) and waist-to-height ratio (WHtR) have been elaborated in our previous study 20 . Blood pressure measurements were performed three times five-minute intervals using an electronic sphygmomanometer (OMRON, HBP-1100, China), and the participants were required to rest for more than ten minutes.…”
Section: Methodsmentioning
confidence: 87%
“…This cross-sectional study reported results from the baseline survey of a Chinese occupational cohort conducted among steelworkers in Tangshan City, Hebei Province in north China. The study design and population have been described in detail in our previous studies 19 , 20 . The main exclusion criteria were diagnosed or suspected secondary causes of hepatic fat accumulation such as excess alcohol intake, or serum hepatitis B surface antigen-positivity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting finding of the current study was the increase in BF% with the duration of exposure to shiftwork irrespective of sex. Supporting the fact, a study conducted by Zhang et al, 57 among a group of female steelworkers, also demonstrated that lengthy duration and high-frequency night shiftwork may increase BF% independent of the BMI. A similar study conducted in the Netherlands reported that shiftwork length seems to be positively linked to BMI and WHR regardless of age, sex, smoking history, physical activity, or education 58 …”
Section: Discussionmentioning
confidence: 69%